GE_GERICHTE C/12977/2013 vom 11. September 2015 - GE Cour de justice (2015)
ACTION EN PAIEMENT D'ENTRETIEN; NOUVEAU MOYEN DE FAIT; ADMINISTRATION DES PREUVES; REVENU HYPOTHÉTIQUE | CC.8; CC.277.2; CC.285.1; CC.279.1